Effect of transurethral resection of the prostate on renal function in patients with renal insufficiency not needing dialysis - Montadhar Hameed Nima; Mohammed Ghanim Alwan; Thaer Saleh Al-Omary (Počki)
Background. The most popular surgical procedure for benign prostatic hyperplasia (ВРН) is still transurethral resection of the prostate (TURP), which is also the “gold standard” by which other surgical (and even medicinal) interventions are evaluated. In many cases of renal failure caused by restriction of the bladder outflow, it restores normal voiding patterns. The purpose: to assess the effect of TURP on renal function in patients with renal insufficiency secondary to ВРН. Materials and methods. A clinical trial study was carried out in the Urology Unit at Al-Yarmouk Teaching Hospital during a period of 18 months from April 1, 2023, till the end of September 2024. It included 71 patients diagnosed with renal dysfunction, which didn’t require renal dialysis and was associated with bladder outlet obstruction due to ВРН, who were prepared to TURP. All patients were sent for serum creatinine evaluation before surgery, then after two weeks from removal of Foley catheter, checking for creatinine was done again. Symptom score was assessed by the International Prostate Symptom Score. Results. After 14 days of surgery, serum creatinine level was significantly decreased compared to that at presentation. The cut point of preoperative creatinine value was 3.1 mmol/L, so creatinine < 3.1 mmol/L before surgery is predictive for improvement of renal function after transurethral resection of the prostate. Bleeding was noticed postoperatively in 7 % of cases. Conclusions. The outcome for renal function following TURP is better for patients with renal insufficiency, whose serum creatinine levels are lower at presentation. ВРН may hasten the evolution of chronic kidney disease in different disease processes, and the etiology of chronic kidney disease is frequently complex.